Development of an intelligent control and energy management system for stratospheric telecommunication airships - Kuttybayeva, Ainur; Zhamalova, Samal; Abdullayev, Mukhit; Zhampeissov, Gaziz; Tazhen, Kalmukhamed; Khabay, Anar; Orazymbetova, Aigul; Kanzhar, Askar; Mechsheryakova, Tatyana; Domrachev, Vladimir (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is an autonomous high-altitude airship platform. This type of high-altitude platform is designed for long-term telecommunication retransmission at altitudes of 18–25 km. The main problem lies in the insufficient stability of flight at the height of the stratosphere and the limited energy capabilities of aircraft. An integrated intelligent control system and energy management have been developed to solve the problems. This architecture in portable form includes a sensor module, an STM32 microcontroller, a LoRa telemetry channel, a mathematical model of dynamics taking into account lift, aerodynamic drag, external factors and atmospheric parameters, and most importantly, a hybrid adaptive PID-fuzzy controller was proposed. Additionally, a model of the energy balance was proposed, which directly interacts with solar panels, energy consumption of drives and battery operation. The simulation data obtained shows that the use of the PID-fuzzy controller provides a significant increase in the stability of the platform. The transition time is reduced by 44.4%, the maximum deviation from the set altitude and flight path is reduced by 56.5%, and the average drive consumption is reduced by 20–22%. The energy balance model demonstrates that the developed system is capable of retaining up to 46% of the battery charge after 24 hours of battery life, which is 18% higher compared to a system without adaptive energy management. The practical significance of the project lies in the possibility of using the developed system as part of autonomous telecommunications networks, balloons, an emergency communication system, remote sensing of the earth, as well as in elements of promising 6G and NTN networks.